Databases and Information Models for Semantic and Evolutionary Analysis in Fortified Cultural Heritage - Sandro Parrinello; Alberto Pettineo (Heritage)
The paper explores two fortified systems, as case studies, to evaluate different modelling approaches, the parameterisation of architectural components, and semantic interpretation, to define a repeatable methodology for classifying, accessing, and sharing architectural information. The use of informational structures to categorise data and relations through semantic attributes addresses the need to make data queryable and interoperable. In architectural documentation, this practice opens up new perspectives for creating and sharing collaborative repositories, radically transforming the way of disseminating and accessing knowledge. Linking qualitative data information with 3D models enables the development of semantic structures that provide a deeper understanding of intrinsic characteristics, historical transformations of architectural complexes, and their cultural context. While databases effectively manage structured information and relationships between different signifiers, semantically enriched 3D modelling, through the management of surfaces or parameters, offers an accurate and flexible representation of each component. The evaluation of these case studies not only improves the ability to understand and appreciate built heritage but also provides new opportunities for researchers in architectural documentation and history. Semantic subdivision processes of built complexes into individual components facilitate the analysis and the digital preservation of heritage, enabling more precise interpretations and faithful reconstructions.